Design of Multi-Part Mould for Production of a Medium-Large Carbon Fibre Component - Skovajsa, Michal; Sedlacek, Frantisek; Mrazek, Martin (Manufacturing Technology Journal, 2020)
This paper deals with the design of a multi-part mould for the production of a carbon fibre medium-large compo-nent. The design and forming of a medium-large component which is defined by a closed structure and has high demands on dimensional accuracy is a very complex process. The goal was to design a simple manufacturing pro-cess for a negative mould. There are many different ways to design and manufacture this type of mould. One pos-sible solution was designed and tested. This paper describes the case study of a carbon fibre monocoque of a small racing car. The first step was to define the requirements of the final product and the negative mould. The next step was to design a multi-part mould with one main parting plane and two minor parting planes and define the number of steps needed to build a negative mould. Another problem is how to define the position of the general anchor points that determine the final product. In this case the procedure of transferring the hole from a positive to a negative mould was defined.
Keywords: Negative Mould; Positive Mould; Carbon fibre; Forming; Monocoque